Portfolio Selection and Purchasing Power Risk–Recent Canadian Experience - Biger, Nahum (Journal of Financial and Quantitative Analysis, 1976)
This paper examined the empirical consequences of explicit consideration of purchasing power risk in portfolio decisions. It was shown that, during a period of significant inflation, the differences between the variance-covariance relations of nominal rates of return and those of real rates of return were sufficiently pronounced to change the composition of investment portfolios. Further, it was shown that the set of real efficient portfolios dominates any investment strategy that ignores purchasing power risk.